Reception. (15th March 2018) - Bridges, Emma; Paul, Joanna
Abstract : With Killing Hercules, Richard Rowland has produced a wide-ranging trans-historical discussion of re-workings of the relationship between the mythical Hercules and Deinaira, from Sophocles' fifth-centurybce Trachiniae to Martin Crimp's 2004 play, Cruel and Tender, and a 2014 staging of Handel's operatic Hercules . Impressive for the breath-taking variety of receptions of the story of Deianira's killing of her husband, the volume devotes as much attention to medieval, post-Reformation, and eighteenth-century versions as to ancient texts (including, as well as Sophoclean tragedy, receptions in Latin – for example, the pseudo-Senecan Hercules Oetaeus and Ovid's Heroides – which lie behind many post-classical re-workings of the story) and contemporary retellings; the study touches on several Italian, French, and German versions as well as those in English. As a scholar who has direct experience of theatre practice, Rowland draws on his involvement in staged versions of both Trachiniae (his own verse translation, which he includes as an appendix) and Cruel and Tender in order to provide fresh insights on both of these texts. The resulting volume, which illustrates the complex and varied reflections on masculinity and sexual identity prompted by the characters of Hercules and Deianira, has at its heart questions relating to the gendered role of violence in retellings of the myth both on a domestic level and in relation to international politics. Hercules has been seen as everything from the epitome of masculine virtue and heroic self-sacrifice to abuser and serial adulterer, 'sexual deviant and disastrous husband' (115); in her turn, Deianira – in some versions denied a voice altogether – has been variously portrayed as duplicitous or insane, or as a victim whose killing of her abuser is deserving of sympathy. The chapter on the Middle Ages illustrates well the re-appropriation of the story to serve a range of political, religious, and social agendas – from condemnation of Hercules' lack of self-control by Augustine to valorization of his sexual violence, as well as the misogynist and misogamist interpretations of Deianira which were marshalled in service of debates on the role of marriage. Elsewhere, Rowland shows how the tale could be used simultaneously on both sides of a single political conflict – during the Civil War period, both regicides and royalists used lines from Seneca's Hercules Furens to insist on the rectitude of their respective stances (153–4). Even those already familiar with the reception of the figure of Hercules will find something new in this rich exploration of the pliability of one mythical story.